Immune Checkpoints in Leprosy: Immunotherapy As a Feasible Approach to Control Disease Progression - Lima, Hayana Ramos; Gasparoto, Thaís Helena; de Souza Malaspina, Tatiana Salles; Marques, Vinícius Rizzo; Vicente, Marina Jurado; Marcos, Elaine Camarinha; Souza, Fabiana Corvolo; Nogueira, Maria Renata Sales; Barreto, Jaison Antônio; Garlet, Gustavo Pompermaier; Silva, João Santana da; Brito-de-Souza, Vânia Nieto; et al. (Frontiers in Immunology, 2017)
Leprosy remains a health problem in several countries. Current management of patients with leprosy is complex and requires multidrug therapy. Nonetheless, antibiotic treatment is insufficient to prevent nerve disabilities and control Mycobacterium leprae. Successful infectious disease treatment demands an understanding of the host immune response against a pathogen. Immune-based therapy is an effective treatment option for malignancies and infectious diseases. A promising therapeutic approach to improve the clinical outcome of malignancies is the blockade of immune checkpoints. Immune checkpoints refer to a wide range of inhibitory or regulatory pathways that are critical for maintaining self-tolerance and modulating the immune response. Programmed cell-death protein-1 (PD-1), programmed cell death ligand-1 (PD-L1), cytotoxic T-lymphocyte-associated protein 4, and lymphocyte-activation gene-3 are the most important immune checkpoint molecules. Several pathogens, including M. leprae, are supposed to utilize these mechanisms to evade the host immune response. Regulatory T cells and expression of co-inhibitory molecules on lymphocytes induce specific T-cell anergy/exhaustion, leading to disseminated and progressive disease. From this perspective, we outline how the co-inhibitory molecules PD-1, PD-L1, and Th1/Th17 versus Th2/Treg cells are balanced, how antigen-presenting cell maturation acts at different levels to inhibit T cells and modulate the development of leprosy, and how new interventions interfere with leprosy development.